The Main Problems of Ukraine International Business (Economic journal of Lesya Ukrainka Volyn National University, 2018)
In the article the basic problems of foreign economic activity of enterprises in Ukraine. The dynamics of exports and imports of goods identified regional and commodity structure of exports and imports, trends and characteristics. Past studies have identified group level and negative factors influence the development of foreign economic activity of enterprises: external (macro-factors of the global environment, financial, economic, institutional, political), direct (intermediate environment-geopolitical, legal and regulatory, regulatory, financial economic); internal (micro- technical, technological, financial, management, staffing). Overview and grouped problems of development and improvement directions of foreign economic activity of enterprises in Ukraine
Keywords: enterprise, foreign economic activity, export, import, balance, management, development